Biomimetic hybrid fibers integrate scaffold topology and bioinert protein cues to harmonize microglial phagocytosis and anti-neuroinflammation - Ming Yin; Chenlong He; Yuwei Wang; Jingwen Qin; Huawei Liu; Han Zhou; Hongyi Zhang; Shan Hua; Shengming Wu; Jing Chen; Keyue Xiao; Qihui Wu; et al. (Chemical Engineering Journal, 2026)

MOF-derived Ni/CeO2 catalyst for photothermal synergistic CO2 methanation: Unveiling the wavelength-dependent contribution - Meirong Dong; Keyue An; Hongchuan Liu; Zehua Huang; Jinke Wu; Youcai Liang; Jidong Lu (Journal of Environmental Chemical Engineering, 2026)

A new sesquiterpene and two new benzoic derivatives from the marine-derived fungus Aspergillus versicolour SCSIO41697 - Qi Cheng; Feng Wu; Keyue Wu; Xumeng Ren; Yiran Lin; Shuhua Qi (Natural Product Research, 2026)

A comprehensive functional landscape of PRV replication and pathogenesis revealed by genome-wide transposon mutagenesis - Wanwan Yan; Keyue Ruan; Lingchao Chen; Songnan Li; Ting Liu; Wu Tong; Fei Gao; Lingxue Yu; Ning Kong; Guangzhi Tong; Hao Zheng (Veterinary Microbiology, 2026)

Effects of PFOA and emerging alternatives at environmental concentrations on murine- and human-derived microglia: A comparative study - Keyue Wu; Shun Zhou; Aoxue Tang; Junyan Tao; Yun Chen; Hao Zhou; Mingdan You (Environmental Research, 2026)

Cross-scenario transfer learning for estimating mangrove nitrogen and phosphorus content from field hyperspectral data to SDGSAT-1 and Sentinel-2 images - Bolin Fu; Yan Wu; Li Zhang; Weiwei Sun; Yeqiao Wang; Tengfang Deng; Hongchang He; Keyue Huang (Remote Sensing of Environment, 2025)

Consumers'Attitudes and Behaviors Toward Circular Food Supply Chain Practices and Sustainable Food Purchase Intention: Evidence from China - Stella Despoudi; Keyue Wu; Evaggelia Nedelkou; Jiayi Zhu (Circular Economy and Sustainability, 2025)
Food supply chain entities have been redesigning their supply chains to become circular. Consumers started to consume food consciously and make more sustainable purchases. Research indicated that there might be an attitude-behavior gap in environmental research. Chinese consumers were heavily affected by COVID-19, which might have impacted their shopping behavior and circular economy actions. This research investigates the attitudes and behaviors of Chinese consumers' regarding their knowledge of circular economy, environmental motivations, and sustainability awareness on sustainable food purchase intention and circular economy practices adoption during COVID-19. Six hypotheses are developed based on the literature review, and a survey questionnaire is deployed. The findings demonstrate that consumers' propensity to engage in sustainable consumption and circular economy behaviors increases directly to their knowledge of such networks. Consumers are more likely to adopt circular economy practices if they have knowledge of the circular food supply chain. However, being environmentally motivated and aware of sustainability does not lead to the adoption of circular economy practices by Chinese consumers. An attitude-behaviour gap is identified regarding the adoption of circular economy practices regarding food packaging. The study’s findings highlight the areas that food supply chain entities and managers should focus on to improve their supply chain’s circularity and consumer engagement. In the end, future research avenues are provided.

New insights into the cytotoxic mechanism of marine-fungus-derived citrinin in three-dimensional Hepa1-6 cell model - Keyue Wu; Qingyue Meng; Xuhua Nong; Xinye Chen; Yonghong Liu; Simon Wing-Fai Mok; Riming Huang; Xiaoyong Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Honokiol attenuates oxidative stress and vascular calcification via the upregulation of heme oxygenase-1 in chronic kidney disease - Xuemin Xian; Xin Zhao; Xingchen Zhou; Hanfang Liu; Changxi Li; Xinquan Wu; Yuhang Chen; Keyue Ye; Hongwei Yang; Mingxi Li; Jianyun Yan; Xiuli Zhang (Toxicology and Applied Pharmacology, 2025)

CLANN: Cloud amount neural network for estimating 3D cloud from geostationary satellite imager - Han Lin; Jun Li; Min Min; Feng Zhang; Keyue Wang; Qunyong Wu (Remote Sensing of Environment, 2025)

Optimal selection of magnesium phosphate cement systems for lunar soil concrete: Potassium, ammonium, calcium, and sodium magnesium phosphate cements - Lingyu Li; Hongfa Yu; Jinmei Dong; Haiyan Ma; Weimin Yu; Keyue Fang; Chengyou Wu; Jing Wen; Weihong Li (Advances in Space Research, 2025)

Responses of surface ozone under the tropical cyclone circulations: Case studies from Fujian Province, China - Keyue Wang; Rui Zhao; Qunyong Wu; Jun Li; Hong Wang; Han Lin (Atmospheric Pollution Research, 2025)

Tracking diarrhea viruses and mpox virus using the wastewater surveillance network in Hong Kong - Xiawan Zheng; Keyue Zhao; Bingjie Xue; Yu Deng; Xiaoqing Xu; Weifu Yan; Chao Rong; Kathy Leung; Joseph T. Wu; Gabriel M. Leung; Malik Peiris; Leo L.M. Poon; et al. (Water Research, 2024)

Development and application of influenza virus wastewater surveillance in Hong Kong - Xiawan Zheng; Keyue Zhao; Xiaoqing Xu; Yu Deng; Kathy Leung; Joseph T. Wu; Gabriel M. Leung; Malik Peiris; Leo L.M. Poon; Tong Zhang (Water Research, 2023)

Antifungal molecular details of MNQ-derived novel carbon dots against Penicillium digitatum - Yongchun Liu; Wei Li; Keyue Wu; Bingfu Lei; Jianying Chen; Xiaoyong Zhang; Hongtao Lei; Xuewu Duan; Riming Huang (Food Chemistry, 2023)

Exploring the role of protein DJ-1 in quality of pale, soft and exudative (PSE) and red, firm and non-exudative (RFN) pork during post-mortem aging - Rui Liu; Keyue Li; Tianyi Yang; Lun Yang; Man Qin; Hai Yu; Mangang Wu; Qingfeng Ge; Wenbin Bao; Shenglong Wu (Food Chemistry, 2023)